Heart remodelling and its role in arrhythmia development in patients with Type 2 diabetes mellitus and arterial hypertension - P. Kh. Dzhanashiya; P. A. Mogutova; N. G. Poteshkina; M. S. Arakelyan (Российский кардиологический журнал)
Left ventricular (LV) remodelling types were investigated in regard to their link to cardiac arrhythmias in patients with Type 2 diabetes mellitus (DM-2) and arterial hypertension (AH) or essential AH (EAH). Hypertrophic LV remodelling types (concentric and eccentric hypertrophy) were more common in individuals with DM-2 and AH or EAH, predicting high-grade ventricular extrasystoles and supraventricular arrhythmias (including paroxysmal atrial fibrillation).